(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the satisfaction of third-year pharmacy students with the educational activities of Hanoi Medical College in 2025. Subjects and methods: A cross-sectional descriptive study was conducted using both quantitative and qualitative approaches among third-year pharmacy students at Hanoi Medical College. Data were collected directly through a self-administered questionnaire and focus group discussions. Results: Students expressed high levels of satisfaction with teaching staff (93.2%, Mean = 4.31) and curriculum (93.11%, Mean = 4.31). Administrative processes and student support services were rated positively, with 89.1% satisfaction (Mean = 4.25). Satisfaction with facilities was lower, at 68.4% (Mean = 3.85). Overall, 91.5% of students reported being satisfied (Mean = 4.21). Conclusion: Third-year pharmacy students reported relatively high satisfaction with the educational activities of Hanoi Medical College. To further enhance training quality, the institution should continue to strengthen its teaching staff while improving aspects related to class and examination scheduling, internet access, the school website, and the service attitudes of administrative personnel.